Chemical constituent characterization and determination of Quisqualis fructus based on UPLC-Q-TOF-MS and HPLC combined with fingerprint and chemometric analysis - Yang, Lin; Dai, Lei; Qin, Weihan; Wang, Yiwu; Zhao, Jianing; Pan, Shuxiang; He, Dan (Frontiers in Plant Science, 2024)
Quisqualis fructus (QF) is a traditional Chinese medicine (TCM) that has a long history in the therapeutic field of killing parasites, eliminating accumulation, and stopping diarrhea, while the therapeutic material basis is ambiguous all the time. The geographical origin differences of QF are also usually ignored in the process of medication. In this study, the alcohol-aqueous soluble constituents in QF from different origins were systematically characterized by ultra-high performance liquid chromatography coupled to quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS). A total of 106 constituents were tentatively characterized in positive and negative ion modes, including 29 fatty acids, 26 organic acids, 11 amino acids and derivatives, 10 glycosides, 9 alkaloids and derivatives, and 21 other constituents. Meanwhile, chemometrics analysis indicated QF from different origins were effectively distinguished and 16 constituents were selected as the potential Q-markers subsequently. Furthermore, an effective and convenient reversed-phase HPLC method was established to simultaneously determine 4 representative components (trigonelline, adenosine, ellagic acid, and 3,3'-di-O-methylellagic acid) in QF samples. HPLC fingerprint analysis indicated that the similarity between 16 batches of QF was in the range of 0.870~0.999. The above results provide some insights for the research on the pharmacodynamic constituents, quality control, and geographical discrimination of QF.